2021
DOI: 10.3390/v13061179
|View full text |Cite
|
Sign up to set email alerts
|

Broad Impact of Exchange Protein Directly Activated by cAMP 2 (EPAC2) on Respiratory Viral Infections

Abstract: The recently discovered exchange protein directly activated by cAMP (EPAC), compared with protein kinase A (PKA), is a fairly new family of cAMP effectors. Soon after the discovery, EPAC has shown its significance in many diseases including its emerging role in infectious diseases. In a recent study, we demonstrated that EPAC, but not PKA, is a promising therapeutic target to regulate respiratory syncytial virus (RSV) replication and its associated inflammation. In mammals, there are two isoforms of EPAC—EPAC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…To prepare RNAs from patient samples, RNAs from 300 µL of NPS, after adding cel-miR-39 as reference controls for sample preparation, were harvested using mir Vana TM Protein and RNA Isolation System from Invitrogen (Waltham, MA, USA, Cat# AM1556), following the manufacturer’s protocol. To harvest RNAs from cell cultures, we used Trizol from Invitrogen (Cat# 15596-026) to extract RNAs as we previously described in [ 20 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare RNAs from patient samples, RNAs from 300 µL of NPS, after adding cel-miR-39 as reference controls for sample preparation, were harvested using mir Vana TM Protein and RNA Isolation System from Invitrogen (Waltham, MA, USA, Cat# AM1556), following the manufacturer’s protocol. To harvest RNAs from cell cultures, we used Trizol from Invitrogen (Cat# 15596-026) to extract RNAs as we previously described in [ 20 , 22 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Trizol-extracted RNAs or RNAs from patient NPS were used to examine viral replication by qRT-PCR, as previously described for RSV or its family member, human metapeumovirus [ 20 , 22 , 23 ]. In brief, to quantify viral genomic copies of RSV, we used primers to assess the genomic part between the N and P regions.…”
Section: Methodsmentioning
confidence: 99%
“…Further studies demonstrated that EPAC1 genetic inhibition inhibits Ebola virus infection in both ex vivo vasculature and endothelial cells independently of the classic cAMP-PKA signaling pathway [ 13 ]. Interestingly, it was recently suggested that EPAC2 may influence different respiratory viral infections from EPAC1 such as those induced by human metapneumovirus, adenovirus infections, and respiratory syncytial virus [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%